Analisis Pengawasan Cukai Hasil Tembakau Di Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean A Jakarta Tahun 2020-2022 - Kuntoro, Triandi; Rahmi, Notika (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The phenomenon of non-tax state revenue (PNBP) from the tobacco sector that has not been optimized makes the Ministry of Finance, Directorate General of Customs and Excise must try to find new solutions and breakthroughs to increase state revenue. Until now, the government continues to optimize the sector. According to Indonesia Law no. 39 of 2007 concerning Amendments to Law no. 11 of 1995 concerning Excise, based on article 1 excise is defined as